The Potential of Moringa oleifera Leaves as a Natural Anti-Stress Ingredient in Fish Feed Based on Qualitative Phytochemical Screening - Junianto Talunga; Reni Lucia Kreckhoff; Rosita A. J. Lintang; Hariyani Sambali; Novie Pankie Lukas Pangemanan; Deiske Adeliene Sumilat; Christina Leta Salaki (Sam Ratulangi University, 2025)
This study aims to evaluate the potential of Moringa oleifera leaves as a natural anti-stress ingredient in fish feed through qualitative phytochemical screening. The extraction was conducted using maceration with 96% ethanol, followed by solvent evaporation using a rotary evaporator and phytochemical assays employing Dragendorff, Wagner, Mayer, AlCl₃, FeCl₃, concentrated H₂SO₄, and froth tests to identify major groups of bioactive metabolites. The results confirmed a very strong presence of alkaloids, along with positive reactions for flavonoids, tannins, saponins, phenolics, and triterpenoids, while steroids were not detected. This metabolite profile indicates antioxidant, immunomodulatory, antimicrobial, and anti-inflammatory activities that are relevant for reducing physiological stress in fish. These findings demonstrate that ethanol extracts of M. oleifera leaves possess practical potential as an anti-stress feed additive capable of enhancing fish resilience to biotic and abiotic stressors in intensive aquaculture. Practically, the use of M. oleifera leaves offers an accessible and economical natural ingredient for the development of functional aquafeed formulations. Keywords: antistress, aquaculture, moringa leaves, phytochemistry, bioactive compounds Abstrak Penelitian ini bertujuan menilai potensi daun kelor (Moringa oleifera) sebagai bahan anti-stres alami dalam pakan ikan melalui skrining fitokimia kualitatif. Ekstraksi dilakukan menggunakan metode maserasi dengan pelarut etanol 96%, diikuti penguapan menggunakan rotary evaporator dan pengujian fitokimia menggunakan pereaksi Dragendorff, Wagner, Mayer, AlCl₃, FeCl₃, H₂SO₄ pekat, serta uji busa untuk mengidentifikasi golongan metabolit bioaktif. Hasil menunjukkan keberadaan alkaloid sangat kuat, serta flavonoid, tanin, saponin, fenolik, dan triterpenoid dengan reaksi positif, sementara steroid tidak terdeteksi. Profil metabolit tersebut mengindikasikan aktivitas antioksidan, imunomodulator, antimikroba, dan antiinflamasi yang relevan untuk menurunkan stres fisiologis pada ikan. Temuan ini menegaskan bahwa ekstrak etanol daun kelor memiliki potensi aplikatif sebagai aditif pakan antistres yang dapat meningkatkan ketahanan ikan terhadap stres biotik dan abiotik dalam budidaya intensif. Secara praktis, pemanfaatan daun kelor berpeluang mendukung formulasi pakan fungsional berbahan alami yang mudah diperoleh dan ekonomis bagi industri akuakultur. Kata kunci: antistres, budidaya, daun kelor, fitokimia, senyawa bioaktif